Development of a Web-Based Library Management Monitoring System at State Senior High School 7 Kupang - Heppy Hanatris Auw; Maria M. B. Sogen; Diana Yanni Ariswati Fallo (Jurnal Teknologi Informatika dan Komputer, 2026)
Happy Hanatris Auw, 2025. Development of a Web-Based Library Management Monitoring System to Improve the Quality of Library Services at SMA Negeri 7 Kupang. Informatics Education Study Program, Faculty of Teacher Training and Education, Citra Bangsa University Kupang. Supervisors: Dr. Maria M. B. Sogen, S.Kom., M.Pd, Diana Yanni Ariswati Fallo, S. Kom., M.T.  This research aims to develop a web-based library management monitoring system to improve service effectiveness and data management accuracy at SMA Negeri 7 Kupang. The method used is Research and Development (R&D) with the Waterfall model, which includes needs analysis, design, implementation, testing, and maintenance. The analysis results show that the previous library management was still done manually, leading to data inaccuracies, service delays, and difficulties in monitoring. The developed system provides features for book and user data management, automated loan and return transactions, real-time stock checking, and integrated report generation. Media expert validation showed a feasibility level of 85.41% with a feasible category. User response testing also yielded excellent results, with 94% of students, 97% of teachers, and 96.2% of librarians. The system implementation proved to speed up services, improve record-keeping accuracy, facilitate information access, and support the development of student character traits such as discipline, responsibility, and independence.